Ibn Rusyd on God and Creationism - Sheyla Nichlatus Sovia (IAIN Kediri, 2019)
Various opinions or atheist ideals are displayed, which assume that the world already exists by itself. As the world is a tirelessly moving machine that has no beginning and no end. That is what has given an assumption that the universe does not have a creator or maintainer so that the term God does not apply in his thoughts and beliefs. This research is library research (Library Research), so that the type of qualitative research. The data source was obtained from Ibn Rusydâ€™s primary data source, Al-Kasyfâ€™ ManÄhij al-Adillat fi Ê»Aqaid al Millat Tahafut at Tahafut and fash al Maqal, the data collection methods used in this study were the deductive, comparative and hermeneutic methods. This research concludes, Ibnu Rusyd proved the existence of God by proposing no propositions, namely the Dalil al Inayah (providence of God), Dalil al-Ikhtira (the proposition of creation), and Dalil al Harakah (the proposition of motion). We witness that everything that has no sense, like for example, natural body, towards the end. The analysis obtained in proving the existence of God by Ibnu Rusyd is acknowledging the existence of God. Their intellect and revelation become the source of knowledge and tools to achieve truth, especially in proving the existence of God. Then his philosophical thought patterns indirectly influenced more by the philosophy of Aristotle. He succeeded in reconciling the world of philosophy with the world of Theology and through his cosmological arguments, has proven the existence of God.Keywords: Ibn Rusyd, Argumentation, God